Polymorphism Thr241Met of the XRCC3 Gene and Lack of Association with Colorectal Cancer Susceptibility Risk among Malaysian Population :A Preliminary Report. - Mohd Aminudin, Mustapha; Ahmad Aizat, Abdul Aziz; Siti Nurfatimah, Mohd Shahpudin; Biswal, Mohan Biswal; Vaik, Venkatesh R.; Zaidi, Zakaria; Shanwani, A. (Japan International Cultural Exchange Foundation (JICEF), 2011)
Background: The genesis of colorectal cancer (CRC) involves a series of steps in which environmental and/or endogenous carcinogens interact with genetic factors and induce or promote cancer development. Genetic polymorphisms in DNA repair genes may influence individual variation in DNA repair capacity and may be associated with a high risk of developing cancer. Studies on the association between DNA repair gene polymorphisms and CRC appear to be limited and nil from Malaysia. Objective: To examine the polymorphism at codon 241 of the X-Ray Cross Complementing group 3 (XRCC3) in 118 CRC cases and 118 normal controls and to investigate the associated risk of this polymorphism for CRC susceptibility. Material and Method: Peripheral blood from the study subjects were collected in EDTA tubes, genomic DNA extracted and XRCC3 Thr241Met genotyped by using PCR-RFLP technique using Nla III restriction enzyme. The resulting genotypes were categorized into wildtype homozygous (Thr/Thr), heterozygous (Thr/Met) and homozygous variant (Met/Met). Results and conclusion: The distribution of genotypes (Thr/Thr, Thr/Met and Met/Met) among CRC cases (83%, 16%, 1% respectively) was not significantly different from those among controls (79%, 21%, 0% respectively). On examining the association between the variant genotypes and CRC risk, the variant genotype either single or in combination did not show significant association with CRC susceptibility risk suggesting that the XRCC3 codon 241 polymorphism does not convey moderate increase in susceptibility to CRC in Malaysian population. Lack of association could be attributed to the small sample size, interaction of other polymorphic DNA repair genes and also low frequency of variant allele for the polymorphism studied in this population.